ChemInform Abstract: Organocatalytic Domino Reaction of Cyanosulfones: Access to Complex Cyclohexane Systems with Quaternary Carbon Centers. Issue 31 (11th July 2013) - Rajkumar, Sundaram; Shankland, Kenneth; Goodman, Jonathan M.; Cobb, Alexander J. A.
Abstract Bifunctional thiourea catalysts are able to control the asymmetric reactivity of nitro‐ and sulfone substituted compounds to generate highly enantioenriched cyclohexane derivatives with up to four contiguous stereocenters, one of which is quaternary in nature.